Features of Regional Antibiotic Resistance in Pharyngeal Infections - Naumenko , Oleksandr; Zashchytynska , Khrystyna (The Ukrainian Scientific Medical Youth Journal, 2025)
Antibiotic resistance (ABR) is a global public health issue. The World Health Organization (WHO) predicts that by 2050, ABR could lead to 10 million deaths annually if no countermeasures are taken (WHO, 2019). The rise in multidrug-resistant (MDR) bacteria and fungi complicates treatment strategies, particularly in healthcare facilities where nosocomial infections are prevalent, according to various studies. To analyze the results of bacteriological examination of throat swabs with antibiograms in pharyngeal diseases and, based on the data analysis, develop recommendations for empirical antibiotic therapy. From 2024 to 2025, 255 throat swabs were collected and cultured at the Brovary Multidisciplinary Clinical Hospital to determine the bacteriological composition of the pharyngeal mucosa and antibiotic resistance. Isolates were identified using standard microbiological methods, such as culturing on nutrient media and biochemical tests. Antibiotic susceptibility was assessed using the minimum inhibitory concentration (MIC) method or the Kirby-Bauer disk diffusion method. Testing was conducted on a panel of antibiotics. Results were interpreted according to standards such as those of the Clinical and Laboratory Standards Institute (CLSI) to classify strains as susceptible, intermediate, or resistant. A multilevel statistical methodology was employed for comprehensive analysis of microbiological data and antibiotic resistance profiles. Data analysis was performed using Python 3.9 and specialized libraries for scientific data processing (NumPy, SciPy, Pandas, and scikit-learn; data visualization was conducted using Matplotlib and Seaborn). Antifungal drugs—clotrimazole (100%) and ketoconazole (90.0%)—demonstrated the highest efficacy in treating fungal infections. Ceftazidime, vancomycin, benzylpenicillin, and clindamycin showed low efficacy (less than 50%), which may indicate high microbial resistance to these drugs. Amikacin, ceftriaxone, and cefepime were the most effective antibiotics for β-hemolytic streptococcus in terms of susceptibility. Staphylococcus aureus exhibited complete susceptibility to levofloxacin, ofloxacin, and meropenem. The study highlights the severity of the antibiotic resistance problem and the need for rational use of antimicrobial agents in clinical practice.